Entre a casa de praia e o imobiliário-turístico: a segunda residência no litoral sergipano - Santos, Priscila Pereira (2015)
In Sergipe, the second house on the coast has two manifestation of content-forms. The traditional way of beach house, usually located on the shoreline or near the sea and the new form, which are the tourist residential complexes, real estate-tourist. From this perspective, the general objective of this research was to analyze the territorial (re) (dis) organization of the coastal area of Sergipe from the territorial manifestations of second homes in the northern coast, specifically in the Barra dos Coqueiros, in the Costa Beach and Atalaia Nova Beach, and South of Sergipe, in Estância town, in the Saco beach and Dunas of Beach. Therefore, the qualitative approach was more appropriate to interpret this phenomenon. The methodological procedures used in the research were: bibliographic research, desk research and field research. The study of traditional beach house and real estate-tourist showed large, complex, relational, multidimensional, well, challenging. Between the beaches of the north coast and the south coast observed differences and similarities in the coastal territorial space for the second residence. As to the form, it was found that the beach houses seem to reflect the purchasing power of the owners. The second house on the South coast shown luxurious, with elegance and sophistication sometimes incomparable to any other Sergipe beach. The territory of the |old| summer home in Saco Beach and Dunas Beach draws on the |strength| of the economic, political and social power in the coastal designed space. In the four analyzed beaches, summer remains |live| as the dominant content of the traditional way of beach house. Family, nature, leisure, heritage, and why not also say social status, present themselves as the |engines| that move the summer in Sergipe coast. In the second residence and leisure housing, is used still the |old| beach house as tourist accommodation. It was found that the coexistence of the territory of the second home and the shelter of territory and survival of permanent residents, the interests of indigenous sometimes converge with the floating population sometimes diverge. In general, cooperation among vacationers, tourists sun and beach and the permanent residents are expressed in generating employment and income. In contrast, we observed several territorial implications that illustrate the environmental conflicts of the |old| form-content beach house. But unlike the spontaneous spread of spend the summer, the implementation of real estate-tourism on the coast of Sergipe was planned and |captured| by the government. The real estate and tourism market, reinvents the summer and the beach house along the lines of differentiation of flexible capital. Differentiated, the |new| form of beach house materializes in tourist residential complexes, |is invented,| the real estate tourism. Anyway, this alliance between the State and the housing-market tourist multiply the density of the use of land resources for second homes in a time never before experienced in the history of Sergipe coast. Between |there| intramural and the |here| to |out| of the wall, the socio-spatial segregation surrounds the |new| form-content of the second residence anchored in the (un) sustainability of said sustainable development.